The Effects of Different Sources of Protein on the Growth Performance and Digestibility Protein of Local Chickens Crossbreed: A Meta-analysis - Alfan Kurniawan; Muhammad Halim Natsir; Suyadi; Danung Nur Adli (Jurnal Ilmu-Ilmu Peternakan, 2023)
A meta-analysis was conducted to determine the effects of different sources of energy on the growth performance and digestibility protein of local chickens crossbreed. A dataset was constructed based on relevant published papers. An algorithm was constructed from 2015 to 2023, with a search in Scopus, Web of Science, PubMed, and Medline using the MESH terms “chicken”, “digestibility”, “local chicken”, “performance”, and “nutrient digestibility”. After careful evaluation, the final dataset consisted of 8 in-vivo studies comprising 31 treatment units. The data analysis and coding were performed using software R version 4.2.1 “Funny-looking kid” computing with library mode (cowplot); (tidyverse); and (viridis); and (nlme). Our meta-analysis with regard to growth performance, the different sources of protein did not affect the body weight, FCR, body weight gain (BWG), final body weight (FBW), and feed intake (FI) (p > 0.05).  In conclusion, the different source of protein negatively affects parameters for growth performance and nutrient digestibility in local chicken crossbreeds.